Complete pathological response and negative postoperative ctDNA were not predictive of discontinuation of adjuvant crizotinib therapy in a patient with locally advanced MET ex14 skipping mutation-positive non-small cell lung cancer: a case report - Wang, Jiantao; Yao, Wenqing; Wang, Weiya; Fan, Mingyu; Huang, Kaili; Liu, Zhenkun; Zhu, Daxing (Frontiers in Oncology, 2023)
Neoadjuvant targeted therapy is an alternative treatment for locally advanced non-small cell lung cancer (NSCLC) patients with driver gene mutation. MET ex14 mutation is considered a driver gene, and crizotinib is the first oral tyrosine kinase inhibitor (TKI) for metastatic MET ex14 mutation-positive NSCLC patients. Here, we reported a case of a locally advanced NSCLC patient harboring MET ex14 mutation who achieved pathological complete response following neoadjuvant crizotinib therapy but developed rapid metastasis due to discontinuation of short-term postoperative adjuvant crizotinib therapy. Although no driver gene mutation was found via next-generation sequencing (NGS) with blood samples before discontinuation of adjuvant crizotinib, the patient was given crizotinib rechallenge. Fortunately, the patient achieved durable complete response. This suggested that neither pathological complete response nor negative circulating tumor DNA (ctDNA) could be an effective predictor for discontinuation of adjuvant targeted therapy. This case report demonstrated the potential of crizotinib as neoadjuvant therapy in MET ex14 mutation-positive NSCLC patients as well as the importance of long-term postoperative therapy even with negative ctDNA in blood.